2016
DOI: 10.4172/2167-1222.1000305
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Thoracotomy in a Swedish Setting: A Consecutive Series of 45 Patients from a Scandinavian Trauma Hospital

Abstract: Background: Emergency thoracotomy (ET) has previously been studied and evaluated in an American and African perspective. The mechanism of injury (MOI) varies between different parts of the world. In the Northern European setting, blunt trauma is the most common MOI. Regarding penetrating thoracic injuries stab wounds compromises the majority whereas gunshot wounds (GSW) are relatively scarce. The aim of this study was to describe the situation at a Scandinavian Trauma Hospital. Method:This study was a retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…2,3 Previous studies have identified overall poor outcomes following RT, particularly in the context of blunt injuries when compared to penetrating trauma. [4][5][6][7][8] Additionally, several factors have been linked to lower likelihoods of survival, including the performance of RT more than 30 min after hospital arrival, RT in the context of traumatic cardiac arrest (TCA), the patient's clinical status on emergency department (ED) arrival, RT procedure duration, heart rate (HR) at the end of the procedure, absence of signs of life (SOL) on-scene or in the ED, and cardiopulmonary resuscitation (CPR) duration. [9][10][11][12][13] However, to date, data have primarily focused on in-hospital and injury-specific variables and literature that synthesizes what we know about outcome predictors in the trauma population following RT is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Previous studies have identified overall poor outcomes following RT, particularly in the context of blunt injuries when compared to penetrating trauma. [4][5][6][7][8] Additionally, several factors have been linked to lower likelihoods of survival, including the performance of RT more than 30 min after hospital arrival, RT in the context of traumatic cardiac arrest (TCA), the patient's clinical status on emergency department (ED) arrival, RT procedure duration, heart rate (HR) at the end of the procedure, absence of signs of life (SOL) on-scene or in the ED, and cardiopulmonary resuscitation (CPR) duration. [9][10][11][12][13] However, to date, data have primarily focused on in-hospital and injury-specific variables and literature that synthesizes what we know about outcome predictors in the trauma population following RT is lacking.…”
Section: Introductionmentioning
confidence: 99%